1998
DOI: 10.1590/s0100-879x1998000500005
|View full text |Cite
|
Sign up to set email alerts
|

Glycosuria in glomerular diseases: histopathology and clinical correlations

Abstract: There are doubts about the presence of glycosuria and the progress of glomerular disease. Some reports suggest that glycosuria could be an index of a more severe tubulointerstitial lesion. We investigated the presence of glycosuria in 60 patients with primary glomerular diseases: 17 patients (28%) had glycosuria and 43 patients (72%) were glycosuria free. The two groups were similar in age, arterial pressure and sex. Serum creatinine was higher in patients with glycosuria (2.0 +/- 1.7 vs 1.3 +/- 0.9 mg/dl, P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…At the same direction, MN patients with glycosuria presented a more severe disease at diagnosis, including higher IFTA, than non-glycosuria MN patients. Similar studies reported higher prevalence of glycosuria in PG (28%) 2,4 . Our lower prevalence may be associated with the fact that we only accounted as glycosuric patients those with glycosuria at the time of diagnosis, whereas other studies have accounted it when present over various periods of the disease.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…At the same direction, MN patients with glycosuria presented a more severe disease at diagnosis, including higher IFTA, than non-glycosuria MN patients. Similar studies reported higher prevalence of glycosuria in PG (28%) 2,4 . Our lower prevalence may be associated with the fact that we only accounted as glycosuric patients those with glycosuria at the time of diagnosis, whereas other studies have accounted it when present over various periods of the disease.…”
Section: Discussionsupporting
confidence: 75%
“…Similar to our findings, these studies reported higher SCr levels, higher Ualb, and lower Salb in the glycosuria group. Additionally, they confirmed higher levels of IFTA and worst renal outcomes in patients with glycosuria 2,4 . Some investigations suggest that tubulointerstitial lesions may correlate better with outcomes in PG than glomerular damage itself 10,11 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the present study, glycosuria ≥ trace was present in 82% of ATIN patients. In the other renal diseases including glomerular diseases, however, glycosuria may also occur due to the concurrent tubular injury [ 11 , 26 ], and glycosuria ≥ trace was present in 15% of patients with other diagnoses. Thus, glycosuria ≥ trace was not very specific to ATIN.…”
Section: Discussionmentioning
confidence: 99%